Investigation of effect of addition of crude palm oil to asphalt pavement mix: a pilot study toward developing a warm mix asphalt - Nur Eleena Nadhirah, Paat (2017)
Study describes on hot mix asphalt (HMA) that requires high manufacture and high temperature to be produced, and prompted discover alternatives approaches to arrange it. Exploration researches the possibility to reduce the temperature of production of HMA and turn into warm mix asphalt (WMA) by addition of crude palm oil (CPO) into the mixtures and reduce emissions from the manufacture and construction of asphalt pavements. The research involves two stages. First stage is to find the optimum asphalt content gradation 14 (AC14) to be used as a control sample. The se ond stage is where few samples will e prepared with addition of . of rude palm oil (CPO) to e mixed in oth normal temperature ( - C) and new temperature ( - C). The samples will e tested ased on Marshall Mix design. Marshall Mix design includes stability, flow, stiffness and void analysis to determine the optimum asphalt content (OAC). Addition of CPO will improve the compatibility of asphaltic concrete mixes in terms of the mixture mechanical characteristics.